Longitudinal analysis of soil erosion dynamics using the RUSLE model in Ethiopia’s Lake Ziway watershed: implications for agricultural sustainability and food security - Teku, Degfie; Workie, Melak Desta (Frontiers in Environmental Science, 2025)
IntroductionSoil erosion is a persistent environmental challenge in Ethiopia’s Lake Ziway Watershed, posing severe risks to agricultural sustainability, food security, and ecosystem stability. Despite its significance, limited longitudinal studies have systematically analyzed soil erosion dynamics in this region or identified critical intervention areas.MethodsThis study employs the Revised Universal Soil Loss Equation (RUSLE) model integrated with remote sensing and GIS techniques to perform a 30-year longitudinal analysis (1993–2023).ResultsThe analysis highlights spatial and temporal trends in both potential and modeled actual soil erosion rates, revealing substantial but fluctuating losses over the study period. In 1993, potential soil erosion ranged from 0 to 2,082 t/ha/yr, totaling approximately 3.76 million tonnes annually. By 2023, this had shifted to a range of 0–2,069 t/ha/yr, with an annual loss of 3.48 million tonnes. Modeled actual soil erosion followed a similar trajectory, decreasing from 2.58 million tonnes in 1993 to 2.30 million tonnes in 2023. Mean soil loss rates for potential erosion increased from 42.91 t/ha/yr in 1993 to 43.73 t/ha/yr in 2023, while modeled actual erosion rates rose from 38.79 t/ha/yr to 41.01 t/ha/yr.DiscussionThese figures consistently exceed Ethiopia’s acceptable soil loss threshold of 10–15 t/ha/y, highlighting the need for targeted interventions, particularly in erosion-prone areas. This study bridges critical knowledge gaps, providing actionable insights for policy development aimed at sustainable land management and agricultural resilience.